Perception and Digital Transformation: A Study of Cloud Accounting Adoption among SMEs in Denpasar - Ni Putu Ayu Nadia Putri; Gusi Putu Lestara Permana; Nur Jannah Mohaidin (Penerbit Goodwood, 2025)
Purpose: To examine how Perceived Ease of Use (PEOU) and Perceived Usefulness (PU) influence Cloud-Based Accounting Effectiveness (CBAE) and, subsequently, Firm Performance (FP) among SMEs in Denpasar. Methodology/Approach: Survey data were collected from 100 SMEs that actively use cloud accounting systems (Jurnal by Mekari, Accurate Online, Kledo, Xero, Zahir Online, QuickBooks). The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) in SmartPLS 4.0 to assess measurement and structural models under the TAM 3 framework. Results/Findings: PEOU and PU significantly enhance CBAE. In turn, CBAE positively affects FP and mediates the effects of PEOU and PU on FP, underscoring system effectiveness as a conduit that translates user perceptions into business outcomes. Conclusions: When cloud accounting is easy to use and perceived as useful, system effectiveness improves, which in turn enhances SME performance in Denpasar. CBAE mediates the effects of PEOU and PU on performance, indicating that real gains arise from effective application, not perceptions alone. Limitations: The study focuses on SMEs in Denpasar and relies on self-reported survey data, which may limit generalizability to other regions or larger firms. Contribution: This research extends TAM 3 by integrating CBAE as a mediating variable and provides empirical evidence that digital accounting adoption drives SME performance. Practical guidance is offered for SME owners, policymakers, and service providers to refine adoption strategies and financial management.